Alloscardovia macacae sp. nov., isolated from the milk of a macaque (Macaca mulatta), emended description of the genus Alloscardovia and proposal of Alloscardovia criceti comb. nov - Killer, J; Ročková, Š; Vlková, E; Rada, V; Havlík, J; Kopečný, J; Bunešová, V; Benada, O; Kofroňová, O; Pechar, R; Profousová, I (International journal of systematic and evolutionary microbiology, 2013)
A novel bacterial strain, designated M8(T), was isolated from milk of a female macaque bred in captivity. The strain was Gram-stain-positive, anaerobic, irregular coccoid-rod-shaped without catalase activity. Analysis of 16S rRNA gene sequence similarity revealed that the isolate was most closely related to Alloscardovia omnicolens CCUG 31649(T) (96.4%) and Metascardovia criceti OMB105(T) (96.6%). Sequences of hsp60, fusA, and xfp genes also confirmed that the strain was most closely related to the type strains of A. omnicolens and M. criceti. The isolate produced fructose-6-phosphate phosphoketolase which is in agreement with classification within the family Bifidobacteriaceae. The major fatty acids were C18 : 1ω9c (35.8%), C16 : 1 (6.2 %) and C14 : 0 (5.7 %). Polar lipid analysis revealed five different glycolipids, two unidentified phospholipids and diphosphatidylglycerol. The peptidoglycan was of the type A4α l-Lys-d-Asp with the presence of d(l)-alanine, d-glutamine, d-asparagine and l-lysine. The DNA G+C content of strain M8(T) was 50.1 mol%. On the basis of genetic, phylogenetic and phenotypic data, strain M8(T) represents a novel species of the genus Alloscardovia for which the name Alloscardovia macacae sp. nov. is proposed. The type strain is M8(T) ( = DSM 24762(T) = CCM 7944(T)). In addition, our results also revealed that Alloscardovia omnicolens DSM 21503(T) and Metascardovia criceti DSM 17774(T) do not belong to different genera within the family Bifidobacteriaceae. We therefore propose to reclassify Metascardovia criceti as Alloscardovia criceti comb. nov. An emended description of the genus Alloscardovia is also provided.
Keywords: Molecular Sequence Data; mléko; Sequence Analysis, DNA; RNA, Ribosomal, 16S; DNA, Bacterial; techniky typizace bakterií; peptidoglykan; Aldehyde-Lyases; Peptidoglycan; Fatty Acids; zastoupení bazí; bakteriální geny; Bacterial Typing Techniques; DNA bakterií; Actinobacteria; aldehydlyasy; sacharidy; Multilocus Sequence Typing; ženské pohlaví; RNA ribozomální 16S; zvířata; Base Composition; Phospholipids; fylogeneze; Macaca mulatta; sekvenční analýza DNA; Milk; mastné kyseliny; Genes, Bacterial; molekulární sekvence - údaje; multilokusová sekvenční typizace; Female; fosfolipidy; Phylogeny; Carbohydrates; Animals